GIANT PARATHYROID ADENOMA AND PARATHYROID CANCER: A CASE SERIES AND LITERATURE REVIEW - Aziz, Hazwani; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Only <1% of cases of primary hyperparathyroidism are due to parathyroid cancer, and 85% are due to parathyroid adenoma. Giant parathyroid adenoma (GPA) is defined as adenoma larger than 3.5 g. CASE Twenty-one cases of parathyroid masses >3.5g in patients with primary hyperparathyroidism who underwent parathyroidectomy in Hospital Putrajaya, Malaysia from 2012 till 2019 were identified. The youngest age was 17 years old, with majority between 50 to 65 years old. Eleven cases presented with nephrolithiasis, 6 cases had osteoporosis and 2 cases were asymptomatic. Average serum calcium was 3.2 mmol/L Average iPTH was 71.5 pmol/L, with highest iPTH 176.6 pmol/L. The sizes vary from 3.5 g to 38 g. 2 cases with adenoma size of 32.4 g and 6 g and ALP 3046 U/L and 405 U/L respectively, developed hungry bone syndrome. Two cases were reported as parathyroid cancer during histopathology examination. First case presented with nephrocalcinosis and chronic pancreatitis, calcium 4.0 mmol/L, iPTH 176 pmol/L and size of 4.2 g. The second case presented with symptomatic hypercalcaemia and osteoporosis, with calcium 3.61 mmol/L, iPTH 88.2 pmol/L and size of 38 g. Another symptomatic case with calcium 2.77 mmol/L, iPTH 87.8 pmol/L and size of 6.9 g had biopsy of atypical parathyroid adenoma with capsular and perivascular invasion. CONCLUSION Differentiating GPA with parathyroid cancer is a challenge as it will determine further surgical intervention.